2017
DOI: 10.1002/cbin.10760
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ATF2 inhibits growth of pancreatic cancer cells and enhances sensitivity to chemotherapy

Abstract: Pancreatic cancer is one of the leading causes of cancer-related death worldwide. Activating transcription factor 2 (ATF2) is a multifunctional transcription factor, and is implicated in tumor progress, yet its role in pancreatic cancer remains unclear. In the present study, the level of ATF2 in pancreatic cancer tissues and the adjacent non-tumorous tissues was detected by quantitative real-time PCR and Western blot. The roles of ATF2 in the proliferation, cell cycle, and apoptosis of pancreatic cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…ATF2 is known to regulate the expression of its target genes, including those involving apoptosis, cell proliferation and DNA damage response ( 6 , 16 ). Accordingly, ATF2 activation has been correlated with the growth of some neoplasms, such as spindle cell carcinoma of the skin ( 17 ), extramammary Paget’s disease ( 18 ), head and neck squamous cell carcinoma ( 19 ), synovial sarcoma ( 20 ) and pancreatic cancer ( 21 ). Interestingly, loss of ATF2 function has also been observed in other malignancies, such as breast and lung carcinomas as well as neuroblastoma ( 22 ), implying that the balance of tissue-specific compositions of ATF2-AP1 dimers is critical for transcriptional programs for cell survival vs cell death ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATF2 is known to regulate the expression of its target genes, including those involving apoptosis, cell proliferation and DNA damage response ( 6 , 16 ). Accordingly, ATF2 activation has been correlated with the growth of some neoplasms, such as spindle cell carcinoma of the skin ( 17 ), extramammary Paget’s disease ( 18 ), head and neck squamous cell carcinoma ( 19 ), synovial sarcoma ( 20 ) and pancreatic cancer ( 21 ). Interestingly, loss of ATF2 function has also been observed in other malignancies, such as breast and lung carcinomas as well as neuroblastoma ( 22 ), implying that the balance of tissue-specific compositions of ATF2-AP1 dimers is critical for transcriptional programs for cell survival vs cell death ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several immunohistochemical studies have determined the expression levels of ATF2, p-ATF2 and/or p-ERK in human tumor specimens. In particular, ATF2 and/or p-ATF2 were found to be significantly elevated in pancreatic cancer ( 21 ), prostate cancer ( 29 ) and spindle cell carcinoma of the skin ( 17 ), compared with respective normal/benign controls. In addition, ATF2 or p-ATF2 overexpression in breast cancer tissues was shown to associate with lower disease-free survival ( P = 0.079) or higher overall survival ( P = 0.047) rates, respectively ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from melanoma, ATF2 was also investigated in pancreatic cancer revealing an upregulation of ATF2 in cancer tissues compared to adjacent non-tumour material (113). Silencing of ATF2 resulted in inhibition of proliferation, induction of apoptosis and rendered tumour cells susceptible to the anti-tumour drug gemcitabine (113).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from melanoma, ATF2 was also investigated in pancreatic cancer revealing an upregulation of ATF2 in cancer tissues compared to adjacent non-tumour material (113). Silencing of ATF2 resulted in inhibition of proliferation, induction of apoptosis and rendered tumour cells susceptible to the anti-tumour drug gemcitabine (113). The oncogenic duality of ATF2 was further studied in bladder cancer where ATF2 activation was shown to be dependent on the androgen receptor (AR) with ATF2 activity being positively correlated to AR-induced urothelial tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that ATF2 is involved in the pathobiology of numerous cancers. For example, ATF2 exhibits oncogenic functions in prostate cancer [7], melanoma [6,8], renal cell carcinoma [9] and pancreatic cancer [10]. Conversely, ATF2 exerts a tumor suppressor role in breast cancer [11] and skin cancer [12], suggesting a tumor-specific characteristic of ATF2 function.…”
Section: Introductionmentioning
confidence: 99%